Protection of mungbean and urdbean crops against vector borne mungbean yellow mosaic virus through botanicals - and N.K. Sharma1, S.K. Singh1, L.P. Awasthi1, Shyam Singh2 (Current Botany, 2011)
<span style="font-size: 8pt; font-family: ";Byington";,";serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The mungbean and urdbean crops were found suffering from the infection of a vector borne virus which was characterized by severe yellowing of the leaves and extremely reduced growth of the plants. Such crops may be protected by the regular spraying either with the aqueous leaf extract of Azadirachta indica, Clerodendrum aculeatum or the root extract of the Boerhaavia diffusa separately. The maximum reduction in the incidence of mungbean yellow mosaic virus disease was observed in mungbean and urdbean when these crops were given six sprays of each botanical separately. In case of C. aculeatum treatments reduction in disease incidence in mungbean and urdbean was 53.76 and 48.22 per cent, respectively. Whereas, B. diffusa root extract could reduce the incidence by 42.48 and 40.55 per cent in mungbean and urdbean followed by 33.07and 28.55 per cent by A. indica. It has been observed that not only the incidence of disease was reduced but a significant increase in plant height, primary and secondary branches, nodulation, pods formation and grain yield was also recorded.